2019
DOI: 10.1111/ped.13898
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of unresponsiveness after initial i.v. immunoglobulin treatment in acute Kawasaki disease

Abstract: Background The aim of this study was to identify the indicators of unresponsiveness to initial i.v. immunoglobulin (IVIG) treatment for Kawasaki disease (KD). Methods One hundred and forty‐five patients with KD, who had received initial treatment consisting of a single IVIG dose (1 g/kg or 2 g/kg) and oral aspirin (30 mg/kg), were studied. Laboratory parameters, including C‐reactive protein (CRP) and serum sodium (Na), were measured before and after IVIG treatment, and during the convalescent phase, and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a meta-analysis that included 13 studies, Zheng et al found significant differences in hyponatremia and factors, such as white blood cell counts, platelet counts, and ALT, in children in the KDSS group compared to the KD group ( 17 ). The pathophysiologic mechanisms of hyponatremia in patients with KDSS can include dehydration, inappropriate antidiuretic hormone secretion syndrome, and acute kidney injury ( 31 , 32 ). Hyponatremia can contribute to the presence of shock because of increased vascular leakage or poor cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis that included 13 studies, Zheng et al found significant differences in hyponatremia and factors, such as white blood cell counts, platelet counts, and ALT, in children in the KDSS group compared to the KD group ( 17 ). The pathophysiologic mechanisms of hyponatremia in patients with KDSS can include dehydration, inappropriate antidiuretic hormone secretion syndrome, and acute kidney injury ( 31 , 32 ). Hyponatremia can contribute to the presence of shock because of increased vascular leakage or poor cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanism remains unknown. Hyponatremia in patients with acute-phase KD is associated with severe in ammation, which results in Kawasaki shock syndrome, IVIG resistance, and CAA development [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%